Praktik Hukum Bisnis Dalam Penetapan Upah Minimum Terhadap Pemenuhan Hak Jaminan Sosial Indonesia - Angelina Yojania; Anasrullah; Siti Nurul Hayah; Khalisah Nur Putriani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Minimum wage determination and the fulfillment of workers social security rights are essential components of labor protection in Indonesia. However, various violations still occur, including wage payments below the minimum standard and low employer compliance in registering workers for social security programs. This study aims to analyze the practice of business law in minimum wage determination and its impact on the fulfillment of workers social security rights in Indonesia. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that minimum wage policies are closely related to the fulfillment of social security rights, as wage levels serve as the basis for calculating contributions and benefits. Nevertheless, implementation remains constrained by low corporate compliance and ineffective labor supervision. Therefore, stronger supervision and greater legal compliance are necessary to ensure optimal protection of workers rights.